1995
DOI: 10.1007/bf01757359
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of purification-associated reduction in IgE-dependent histamine release from rat peritoneal mast cells

Abstract: Histamine release from purified rat peritoneal mast cells (PMC) was examined and compared to that from a non-purified preparation (PEC). Both PEC and PMC released similar amounts of histamine upon stimulation with compound 48/80, calcium ionophore A23187 and substance P. In contrast, IgE-dependent histamine release from PMC caused by antigen, anti-IgE and concanavalin A was very low compared to that of PEC. The reduced IgE-dependent histamine release from PMC, however, was recovered when PMC was reconstituted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
4
11
0
Order By: Relevance
“…Purification reduced the histamine release from peritoneal mast cells as reported previously [4,5]. These results indicate that mesenteric mast cells release higher rates of histamine than peritoneal mast cells.…”
Section: Japansupporting
confidence: 86%
See 4 more Smart Citations
“…Purification reduced the histamine release from peritoneal mast cells as reported previously [4,5]. These results indicate that mesenteric mast cells release higher rates of histamine than peritoneal mast cells.…”
Section: Japansupporting
confidence: 86%
“…A bellshaped dose-response curve was obtained, and over 50% of total histamine was released at an optimal antigen concentration, 10 µg/ml. The dose-response curve is almost comparable to that obtained with peritoneal mast cells reported previously [4,5]. Results of the kinetic study are shown in Fig.…”
Section: Japansupporting
confidence: 86%
See 3 more Smart Citations